Habituation of crossbred beef calves to corral handling reduces their reactivity and improves performance - Grajales-Cedeño, Joseph K. [UNESP]; Paranhos da Costa, Mateus J.R. [UNESP] (Elsevier, 2024)
The study aimed to determine the role of the habituation process of crossbred beef calves to corral handling on their reactivity, welfare and performance. Thirty-nine calves aged 87.69 ± 19.93 days were randomly divided into two treatments according to their weight, sex, and reactivity, as follows: 1) calves habituated to corral handling (HAB, N = 21) and 2) calves not habituated to corral handling, control group (NHAB, N = 18). The habituation process to corral handling was performed for 15 minutes twice a week for two weeks to reduce the animals' flight distance from humans. Calves' reactivities were scored when keeping them inside a scale and a squeeze chute (by applying scores ranging from 1 to 5 in both situations) and by scoring the speed at which they exited the squeeze chute (1 = walking or 2 = trotting and running). The assessments of physiological (heart rate, respiratory rate, and rectal temperature) and performance (average weight gain and weaning weight adjusted to 205d) indicators were carried out before (d-10), just after (d17) and 150 days after finishing the habituation process (d150). Mixed linear models were used to evaluate the fixed effects of treatments, assessment moments, and sex on most dependent variables, except for flight speed, which was analyzed using the Chi-square test. The HAB calves showed lower reactivity scores in d17 and 150 than NHAB calves in both measurements, scale and squeeze chute. Furthermore, a higher percentage of HAB calves exited the squeeze chute walking than NHAB calves in d17 and d150 (62 % vs 11 % and 24 % vs 5 %, respectively). None of the physiological variables was affected significantly by treatments. HAB calves showed greater ADG (p=0.0007) and reached a higher adjusted weaning weight to 205d (p=0.004) than NHAB calves. In conclusion, habituation to corral handling reduces reactivity and improves the performance of crossbred beef calves.
Keywords: Animal welfare; Beef cattle; Behavior; Human-animal interactions; Learning process